2023
DOI: 10.1371/journal.pone.0282040
|View full text |Cite
|
Sign up to set email alerts
|

Sixteen years of innovation in youth mental healthcare: Outcomes for young people attending Australia’s headspace centre services

Abstract: Australia’s headspace initiative is world-leading in nation-wide youth mental healthcare reform for young people aged 12 to 25 years, now with 16 years of implementation. This paper examines changes in the key outcomes of psychological distress, psychosocial functioning, and quality of life for young people accessing headspace centres across Australia for mental health problems. Routinely collected data from headspace clients commencing an episode of care within the data collection period, 1 April 2019 to 30 M… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 25 publications
1
17
0
Order By: Relevance
“… 19 22 The organisations headspace Australia and Jigsaw Ireland have published outcome evaluation analyses, comparing first and last visit data. 19 21 Among young people who sought support from headspace Australia, 29.9% improved reliably (37.8% clinically significantly) in terms of social and occupational functioning, and 24.5% improved reliably (22.4% clinically significantly) regarding psychological distress. 21 Jigsaw Ireland reported that 62% of the young people who used their service improved clinically significantly and reliably with regard to psychological distress.…”
Section: Worldwide Research Findingsmentioning
confidence: 99%
See 2 more Smart Citations
“… 19 22 The organisations headspace Australia and Jigsaw Ireland have published outcome evaluation analyses, comparing first and last visit data. 19 21 Among young people who sought support from headspace Australia, 29.9% improved reliably (37.8% clinically significantly) in terms of social and occupational functioning, and 24.5% improved reliably (22.4% clinically significantly) regarding psychological distress. 21 Jigsaw Ireland reported that 62% of the young people who used their service improved clinically significantly and reliably with regard to psychological distress.…”
Section: Worldwide Research Findingsmentioning
confidence: 99%
“… 19 21 Among young people who sought support from headspace Australia, 29.9% improved reliably (37.8% clinically significantly) in terms of social and occupational functioning, and 24.5% improved reliably (22.4% clinically significantly) regarding psychological distress. 21 Jigsaw Ireland reported that 62% of the young people who used their service improved clinically significantly and reliably with regard to psychological distress. 19 Furthermore, Youth Information, Advice and Counselling Services (YIACS) across England reported that 52.2% improved reliably and 29.4% clinically significantly with regard to psychological distress (Clinical Outcomes in Routine Evaluation 10 [CORE-10]), which was 37.2% and 36.4%, respectively, for the Young Person's CORE (YP-CORE).…”
Section: Worldwide Research Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Headspace services provide holistic support for young people aged between 12 and 25 years, encompassing mental, physical and sexual health. They also provide support on drugs and alcohol and for issues relating to employment and education (Rickwood et al, 2023). Evaluations of these services have indicated that the majority of young people access the service for support with symptoms of anxiety and depression, and that around a third show significant improvements in psychological distress and psychosocial functioning (Rickwood et al, 2015).…”
Section: Solutions and Innovationsmentioning
confidence: 99%
“…Evaluations of these services have indicated that the majority of young people access the service for support with symptoms of anxiety and depression, and that around a third show significant improvements in psychological distress and psychosocial functioning (Rickwood et al, 2015). Just over two-thirds of service users show significant improvements in either psychological distress, psychosocial functioning or self-reported quality of life (Rickwood et al, 2023).…”
Section: Solutions and Innovationsmentioning
confidence: 99%